Le divorce dans l’Antiquité classique : perspective comparatiste - Jean-Baptiste Bonnard; Camille Noûs (Genre & Histoire)
Divorce existed in Classical Antiquity (Greek and Roman worlds, 5th century BCE – 2nd century CE), but it differed significantly from the modern homonymous reality in several features which have more to do with the distinctly patriarchal structures of these ancient societies. The free women attached to civic communities were in fact, apart from exceptions, placed under the authority of a man (usually their father) who, by giving them in marriage, could transmit this authority to the husband. In these circumstances, divorce, which was most often initiated by the husband, when it was not the father, was more akin to a repudiation than to a divorce in the sense in which we now understand it. However, divorce on the wife's initiative didexist, to a certain extent, but this did not imply any equality of status between the spouses. The differences between the Greek world and Rome are also noticeable both in terms of the nature of the authority exercised over women as well as in the motivations and modalities of divorce.